Physiological and genomic characterization of Arcobacter anaerophilus IR-1 reveals new metabolic features in Epsilonproteobacteria - Roalkvam, Irene; Drønen, Karine; Stokke, Runar; Daae, Frida Lise; Dahle, Håkon; Steen, Ida Helene (Frontiers in Microbiology, 2015)
In this study we characterized and sequenced the genome of Arcobacter anaerophilus strain IR-1 isolated from enrichment cultures used in nitrate-amended corrosion experiments. A. anaerophilus IR-1 could grow lithoautotrophically on hydrogen and hydrogen sulfide and lithoheterothrophically on thiosulfate and elemental sulfur. In addition, the strain grew organoheterotrophically on yeast extract, peptone and various organic acids. We show for the first time that Arcobacter could grow on the complex organic substrate tryptone and oxidize acetate with elemental sulfur as electron acceptor. Electron acceptors utilized by most Epsilonproteobacteria, such as oxygen, nitrate and sulfur, were also used by A. anaerophilus IR-1. Strain IR-1 was also uniquely able to use iron citrate as electron acceptor. Comparative genomics of the Arcobacter strains A. butzleri RM4018, A. nitrofigilis CI and A. anaerophilus IR-1 revealed that the free-living strains had a wider metabolic range and more genes in common compared to the pathogen strain. The presence of genes for NAD+-reducing hydrogenase (hox) and dissimilatory iron reduction (fre) were unique for A. anaerophilus IR-1 among Epsilonproteobacteria. Finally, the new strain had an incomplete denitrification pathway where the end product was nitrite, which is different from other Arcobacter strains where the end product is ammonia. Altogether, our study shows that traditional characterization in combination with a modern genomics approach can expand our knowledge on free-living Arcobacter, and that this complementary approach could also provide invaluable knowledge about the physiology and metabolic pathways in other Epsilonproteobacteria from various environments.